Integrated metagenomics and metabolomics analyses revealed biomarkers in β-casein A2A2-type cows - Zhao, Jinyan; Wang, Chuanchuan; Hu, Jiahuan; Ma, Ruoshuang; Yu, Baojun; Zhao, Wei; Wang, Hua; Gu, Yaling; Zhang, Juan (Frontiers in Veterinary Science, 2024)
In Holstein cows, β-casein, one of the most critical proteins in milk, exists in two main genotypes, A1 and A2. Herein, 45 Holstein cows [categorized into three groups based on β-casein A1A1, A1A2, and A2A2 genotypes (N = 15)] with the same feeding management and litter size were enrolled to explore differences in rumen microflora and metabolites across various β-casein genotypes. Rumen fluids were collected for metagenomics and metabolomics analyses. Metabolomics and weighted gene co-expression network analysis (WGCNA) revealed that arachidonic acid (AA), adrenic acid (AdA), glycocholic acid (GCA), and taurocholic acid (TCA) were significantly and positively correlated with milk fat % in dairy cows (p < 0.05). Furthermore, macro-genomics and Spearman’s correlation analysis revealed significant positive correlations (p < 0.05) between the characteristic flora (g_Acetobacter, g_Pseudoxanthomonas, g_Streptococcus, and g_Pediococcus) and the five characteristic metabolites in the rumen of A2A2 dairy cows. Moreover, functional enrichment analysis revealed more genes enriched to the TRP channel’s inflammatory mediator-regulated pathway and the mTOR signaling pathway in A2A2 genotyped cows. Additionally, the regulatory effects of AA on bovine mammary epithelial cells (BMECs) were examined using CCK-8, EdU, and qRT-PCR assays, revealing that AA promoted triglyceride (TG) synthesis and upregulated the milk fat marker genes including SREBF1, ACSS2, AGPAT6, and FASN. Overall, we identified characteristic microorganisms and metabolites in A2A2 Holstein cows and established that AA could be a biomarker for higher milk fat %.